Longitudinal assessment of symptoms and risk of SARS-CoV-2 infection in healthcare workers across 5 hospitals to understand ethnic differences in infection risk. (April 2021) - Valdes, Ana M.; Moon, James C.; Vijay, Amrita; Chaturvedi, Nish; Norrish, Alan; Ikram, Adeel; Craxford, Simon; Cusin, Lola M.L.; Nightingale, Jessica; Semper, Amanda; Brooks, Timothy; McKnight, Aine; et al.
Abstract: Background: : Healthcare workers (HCWs) have increased rates of SARS-CoV-2 infection compared with the general population. We aimed to understand ethnic differences in SARS-CoV-2 seropositivity among hospital healthcare workers depending on their hospital role, socioeconomic status, Covid-19 symptoms and basic demographics. Methods: A prospective longitudinal observational cohort study. 1364 HCWs at five UK hospitals were studied with up to 16 weeks of symptom questionnaires and antibody testing (to both nucleocapsid and spike protein) during the first UK wave in five NHS hospitals between March 20 and July 10 2020. The main outcome measures were SARS-CoV-2 infection (seropositivity at any time-point) and symptoms. Registration number: NCT04318314. Findings: 272 of 1364 HCWs (mean age 40.7 years, 72% female, 74% White, ≥6 samples per participant) seroconverted, reporting predominantly mild or no symptoms. Seropositivity was lower in Intensive Therapy Unit (ITU) workers (OR=0.44 95%CI 0.24, 0.77; p=0.0035). Seropositivity was higher in Black (compared to White) participants, independent of age, sex, role and index of multiple deprivation (OR=2.61 95%CI 1.47-4.62 p=0.0009). No association was seen between White HCWs and other minority ethnic groups. Interpretation: In the UK first wave, Black ethnicity (but not other ethnicities) more than doubled HCWs likelihood of seropositivity, independent of age, sex, measured socio-economic factors and hospital role.